Adherence to application technique of inhaled corticosteroid in patients with asthma and COVID-19 improves outcomes - Tichopád, Aleš; Žigmond, Jan; Jeseňák, Miloš; Solovič, Ivan; Breciková, Katarína; Rybář, Marian; Rožánek, Martin; Sedlák, Vratislav (BMJ open respiratory research, 2024)
BACKGROUND: Inhaled corticosteroids have been widely reported as a preventive measure against the development of severe forms of COVID-19 not only in patients with asthma. METHODS: In 654 Czech and Slovak patients with asthma who developed COVID-19, we investigated whether the correct use of inhaler containing corticosteroids was associated with a less severe course of COVID-19 and whether this had an impact on the need for hospitalisation, measurable lung functions and quality of life (QoL). RESULTS: Of the studied cohort 51.4% had moderate persistent, 29.9% mild persistent and 7.2% severe persistent asthma. We found a significant adverse effect of poor inhaler adherence on COVID-19 severity (p=0.049). We also observed a lower hospitalisation rate in patients adequately taking the inhaler with OR of 0.83. Vital capacity and forced expiratory lung volume deterioration caused by COVID-19 were significantly reversed, by approximately twofold to threefold, in individuals who inhaled correctly. CONCLUSION: Higher quality of inhalation technique of corticosteroids measured by adherence to an inhaled medication application technique (A-AppIT) score had a significant positive effect on reversal of the vital capacity and forced expiratory lung volume in 1 s worsening (p=0.027 and p<0.0001, respectively) due to COVID-19. Scoring higher in the A-AppIT was also associated with significantly improved QoL. All measured variables concordantly and without exception showed a positive improvement in response to better adherence. We suggest that corticosteroids provide protection against the worsening of lungs in patients with COVID-19 and that correct and easily assessable adherence to corticosteroids with appropriate inhalation technique play an important role in preventing severe form of COVID-19.
Keywords: Inhaler devices; Forced Expiratory Volume; Inflammation; Viral infection; COVID-19; kvalita života; Asthma Guidelines; lidé; hormony kůry nadledvin; Quality of Life; bronchiální astma; usilovný výdechový objem; Humans; Adrenal Cortex Hormones; Asthma Epidemiology; Asthma; Respiratory Infection